THE NATURE OF THE ADVERTISING IMAGE USING THE EXAMPLE OF RESIDENTIAL REAL ESTATE ADVERTISING - Sknarev, Dmitry; Trubnikova, Nina (Revista Inclusiones, 2020)
The nature of the Russian residential real estate market underlies the relevance of the present study. This virtually unexplored advertising topic is of special interest to researchers from marketing and philological perspectives. The aim of the present study was to examine the specific features of creating the advertising image in marketing communications and to analyze it using residential real estate advertisements. The study is based on print and online advertisements as well as construction company and residential neighborhood websites. Various methods and techniques were used to achieve the above-mentioned research objective: analytical and theoretical, systems and pragmatic methods, quantitative method, continuous sampling method involving linguistic means, techniques and marketing text units creating product images, based on print and online advertisements; method of semantic interpretation and identification, linguistic statistics’ quantitative and symptomatic technique and surveying. Linguistic means and techniques for creating the advertising image were investigated in terms of semantics, pragmatics and linguistic marketing. In analyzing linguistic means, it was discovered that advertising memes (tegemes and detalemes) are important for the creation of the residential real estate image in marketing communications. The identified features of the advertising image include stability, adaptability, interactivity and sociocultural implications.